Konsep dan Teori Kepemimpinan Pendidikan: Suatu Pemahaman Teks Bahasa Arab pada Buku Al Idaroh Tarbawiyah - Yanti Fatmariyanti; Suhada Marwah (PASCASARJANA UNISNU, 2023)
The existence of leadership as part of a management is very important to achieve organizational goals. It has strategic and dominant roles due to its position in managing an organization. This article written aims to describe the understanding of educational leadership by examining problems through library research, according to the book written by Dr. Ahmad Bittoh, Dr. Hasan At-toani entitled Al Idaroh Tarbawiyah. The method used in writing this article is a qualitative method. To understand whether educational leadership must first know the definition, concept and theory of leadership itself, especially in leadership Islamic educational institutions should concern the four characteristics of leadership according to Islam, namely shiddiq, amanah, tabligh, and fathonah.Keywords: Educational leadership; Concept; Theory